PRODUCT TRADEMARK DISPUTE SETTLEMENT “BABY CARE” (STUDY OF DECISION NUMBER 89/PDT-SUS BRAND / 2022/PN.NIAGA /JKT.PST) - Lumban Gaol, Daniel; Saidin, OK.; Maharani Barus, Utary (SIBATIK JOURNAL: Jurnal Ilmiah Bidang Sosial, Ekonomi, Budaya, Teknologi, Dan Pendidikan, 2025)
The development of information technology and transportation has supported the globalization of intellectual property rights. Globalization has opened the door for products and services to cross national borders and create new opportunities and challenges. Increasingly sophisticated technology and transportation enable the movement of goods and information quickly and efficiently around the world. The sustainability of economic growth depends strongly on the stability of public consumption and is supported by income growth in sectors such as agriculture, industry, and services. In the context of Intellectual Property Rights, such as brands, globalization has major implications. Products and brands that are already known locally can easily add to the global market. However, with this opportunity also comes the risk of counterfeiting and unfair competition. Therefore, the importance of protecting intellectual property rights is very important to ensure that innovation and intellectual works receive proper recognition and protection at the global level.